2016
DOI: 10.1073/pnas.1603395113
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Alberti: Are in vitro folding experiments relevant in vivo?

Abstract: In his letter, Alberti (1) does not challenge any of the central results in our paper (2), including the main proof that upward curvature in the logarithm of the unfolding rate of a protein as a function of an applied mechanical force implies that underlying energy landscape is multidimensional. However, he wonders if the switch in pathway in Src tyrosine kinase SH3 (Src homology 3) domain discovered in single-molecule pulling experiments (3, 4) applies to "living cells/ physiological settings," an issue that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…We argued that because SH3 has only one dominant pathway, HI has less of an effect on the folding rate as that of CI2 at T< f T . Additionally, several single molecule pulling experiments have also shown that the addition of more than one order parameter is necessary to describe folding [56,57]. Even though Woodside and coworkers have shown that it is possible to use a single reaction coordinate to characterize the entire folding landscape for a specific protein, they are not able to claim that it is possible for all proteins, however [58].…”
Section: B Underlying Kinetic Principles Of the Crossover Behaviormentioning
confidence: 99%
“…We argued that because SH3 has only one dominant pathway, HI has less of an effect on the folding rate as that of CI2 at T< f T . Additionally, several single molecule pulling experiments have also shown that the addition of more than one order parameter is necessary to describe folding [56,57]. Even though Woodside and coworkers have shown that it is possible to use a single reaction coordinate to characterize the entire folding landscape for a specific protein, they are not able to claim that it is possible for all proteins, however [58].…”
Section: B Underlying Kinetic Principles Of the Crossover Behaviormentioning
confidence: 99%
“…The most obvious achievement lies in its broad applicability and it is now possible to directly compare the results of experiments recorded at vastly different pulling speeds. A very important issue is concerned with the possible speed-dependent change in the pathway of mechanical unfolding, in particular the crossover from thermal to mechanical unfolding [29,49]. Also the impact of dynamic disorder in the mechanical unfolding can be investigated over a huge range of rates and thus might allow to probe different regimes of this fascinating topic [50].…”
Section: Discussionmentioning
confidence: 99%
“…26 Recently, simulated AFM was applied to investigate unfolding of the cold shock protein B (Csp) 27 and the Src SH3 domain. 28 SMD has also been used to probe mechanical resistance of peptide-receptor interactions. 29 In this study, we hypothesized that, under MD-simulated stress, models with a high structural similarity to their native conformation would be more resistant to unfolding than models with more inaccurate folds.…”
Section: Introductionmentioning
confidence: 99%
“…Early applications of SMD used to mimic AFM on biological systems were performed by the Schulten group to study the unbinding of the avidin‐biotin complex 24 and the unfolding pathway of titin IG domains, 25 which showed good agreement with contemporary experiments using AFM 26 . Recently, simulated AFM was applied to investigate unfolding of the cold shock protein B (Csp) 27 and the Src SH3 domain 28 . SMD has also been used to probe mechanical resistance of peptide‐receptor interactions 29 …”
Section: Introductionmentioning
confidence: 99%